Who bears the burden of bribery? Evidence from public service delivery in Kenya. (15th November 2017) - Mbate, Michael
Abstract: This article empirically examines how an individual's economic, social and political capital affects their propensity to make bribe payments in exchange for public services. Using an individual‐level survey on bribes, the econometric results suggest that the burden of bribery is borne by the poor, but substantially decreases when institutions that constrain bureaucratic corruption are strong and effective. The results also show that the incidence of bribery decreases when social capital is high but increases when political networks are prevalent. These findings support the need to combine anti‐corruption reforms with poverty reduction strategies and social policies in order to foster equity in public services provision in Kenya.